THE MEDIATING EFFECT OF QRIS ON THE RELATION BETWEEN DIGITAL MARKETING AND PRODUCT INNOVATION ON BUSINESS PERFORMANCE - Nabiila Mega Devina; Ngatno Ngatno; Hari Susanta Nugraha (Universitas Diponegoro, 2026)
Abstract: Batik MSMEs (Micro, Small, and Medium Enterprises) in Yogyakarta, rooted in Indonesia’s cultural heritage, face growing challenges to remain competitive in the digital era. This study explores how QRIS (Quick Response Code Indonesian Standard) mediates the relationship between digital marketing and product innovation on business performance. It aims to provide actionable insights to help Batik MSMEs embrace innovation and improve their competitiveness. This study used quantitative approach with explanatory research design, which data were collected through questionnaires from Batik MSMEs in Yogyakarta. The findings reveal both digital marketing and product innovation significantly and positively affect QRIS usage and business performance. Furthermore, QRIS mediates the relationship between these variables and enhances their impact on business outcomes. These results highlight the importance of QRIS adoption in optimizing the synergy between digital marketing and product innovation to improve business performance. This study offers valuable insights for Batik MSMEs, encouraging the integration of digital tools to foster sustainability and growth in the creative economy sector.